Incorporating critical thinking skills (CTS) in ESL classroom: its implementation and problems / Zainab Ab. Rahman - Ab. Rahman, Zainab (2006)
The purpose of this study was to investigate whether teachers incorporate critical thinking skills in the ESL classrooms. This was done by looking at the level of the questions which were most frequently asked by teachers and the activities that were frequently carried out in classrooms based on the Bloom's taxonomy. This study was also carried out to find out the problems that these teachers encountered while implementing critical thinking skills in their English lessons. The data concerning teachers' classroom practice, their knowledge on critical thinking skills and their problems in incorporating the skills were gathered through a 40-item questionnaire involving 20 teachers from 2 schools, SMK Kompleks Gong Badak and SMK Manir, in Kuala Terengganu. Informal interviews with the 2 panel heads of the schools were also conducted to support the responses given in the questionnaire by these teachers. The findings of this study indicated that teachers realized the importance of critical thinking skills and had the knowledge on these skills. However, the skills were not frequently incorporated into lessons. This is due to the fact that these teachers had difficulties in carrying out activities to promote critical thinking skills in classrooms due to some constraints such as lack of time, their focus on examination, students’ proficiency and’ attitude, whereby, they always waited for their teachers for information.